Estudio de corrosividad atmosférica en el Volcán Turrialba - Pridybailo-Chekan, Galina; Jimenez-Salas, Ronald; Álvarez, Juan Fernando (Instituto Tecnológico de Costa Rica, 2011)
In February 2008, it requested by the investigators OVSICORI The National University School of Science and Engineering of Materials Costa Rica Institute of Technology study corrosion in an area near the crater of the Turrialba Volcano, since the last year has increased fumes in the volcano and has been detected effects on vegetation and deterioration in the materials found in that area. Given the experience you have in studies on this subject in previous projects, a study of atmospheric corrosion rate proposed in the volcano, both qualitative and quantitative. The project to the Vice Presidency of Research and proposes a preliminary phase starts to locate the place of study with the support of OVSIVCORI and with the prior preparation of a station atmospheric corrosion. Methodology study atmospheric corrosion field is applied, using specimens of steel, copper, aluminum and galvanized steel for the quantitative study ISO (corrosion rate) standard, and for qualitative studies are placed common materials used in the environment of the Turrialba volcano. ICE later learns of this project and other materials supplied by them to be exposed to corrosion Station. Also support ICE Corrosion Center for analysis of contaminants (chlorides and SO 2) is received detectors and meteorological data of temperature and relative humidity are installed in the station study. This report includes an introduction of the mechanism of atmospheric corrosion, in the introductory part of this paper, the methodology developed, the discussion of the results and recommendations based on these results.
Proyecto de Investigación (Código 5402 1490) Instituto Tecnológico de Costa Rica. Vicerrectoría de Investigación y Extensión (VIE). Escuela de Ciencia e Ingeniería de los Materiales, 2011
Keywords: Corrosión; Gases; Condiciones; Contaminantes; Lluvia ácia; Acero